Strategi Komunikasi Corporate Social Responsibility (CSR) Donor Darah McDonald’s Kota Solo dalam Meningkatkan Partisipasi dan Kesadaran Masyarakat - Ulfah Farida; Esfandani Indreswari; Rahmat Wisudawanto (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study aims to explore the communication strategies implemented in the Corporate Social Responsibility (CSR) blood donation activities organized by McDonald’s in Solo City. The research adopts a descriptive qualitative approach to gain a comprehensive understanding of how communication plays a role in the success of these CSR initiatives. Data were collected through in-depth interviews with relevant stakeholders, direct observations during the CSR events, and the analysis of documentation related to the activities. The findings reveal that interpersonal communication is a key factor in the effective implementation of blood donation CSR programs at McDonald’s Solo City. This approach enables the establishment of strong relationships with strategic partners, particularly the Indonesian Red Cross (Palang Merah Indonesia/PMI) Solo City, which serves as the main collaborator in organizing the events. Furthermore, McDonald’s successfully engages and mobilizes opinion leaders within the community to disseminate information widely and encourage public participation. These opinion leaders, trusted by the local community, play an important role in influencing people’s awareness and willingness to participate in the blood donation activities. The success of the program is also supported by consistent follow-up communication, mutual trust, and the ability to adapt messages to the cultural and social context of the target audience. In conclusion, the research highlights that well-developed interpersonal communication strategies—characterized by trust, collaboration, and community engagement—significantly contribute to the effectiveness and sustainability of CSR blood donation programs. These findings imply that companies aiming to enhance their CSR initiatives should prioritize building and maintaining strong interpersonal communication channels with both partners and the community to achieve impactful and long-term results.